Pengawasan Kualitas Inspektur Pada Keamanan Penerbangan Di Area Terminal Bandar Udara Internasional Sultan Hasanuddin Makassar - Bintang Putro Ramadan; Amelia P Tamara (Universitas Maritim AMNI Semarang, 2023)
The Region V Airport Authority Office as UPT (Technical Implementation Unit) within the Ministry of Transportation is under the auspices and is responsible to the Minister of Transportation through the Director of Air Transportation. The function of the Region V Airport Authority is to supervise, control, and regulate aviation activities. This research aims to find out (1) How is the quality of the Inspector's supervision of flight security in the terminal area of Sultan Hasanuddin International Airport Makassar, (2) The obstacles faced by aviation inspectors in the avsec field and the efforts made by inspectors in conducting surveillance in the terminal area of Sultan Hasanuddin International Airport Makassar. This research was conducted at the Makassar Region V Airport Authority Office, in February - March 2023, this research uses descriptive research with qualitative analysis. The data in this study used primary and secondary data, data collection in this study was by interview, observation and documentation. And the tringulation technique to test the reliability of the data. The results of the discussion in this study are (1) the quality supervision of inspectors on aviation security in the terminal area is good as evidenced by training, field practice and has followed applicable regulations such as PM 41 of 2011 which contains airport authority inspectors only as regulators who carry out supervision of activities in the field. (2) and the obstacles faced by inspectors in the terminal area, namely limited security area cooking permits for this obstacle, the inspectors have carried out surveillance of the avsec and if the inspectors find that the person is categorized as endangering flight activities, the inspectors take action against the person without having to contact the avsec on duty in the terminal area, office busy hours for the office busy hours themselves, the inspectors use breaks or office hours to keep monitoring in the terminal area, and finally the culture as the inspectors themselves are firm and give an appeal that the actions they take are wrong.